Investigating Indonesian EFL Learners’ Cognitive Language Learning Strategy Within Blended Learning In The Covid-19 Pandemic - Andris Susanto, Dias; Egar , Ngasbun; Sumardiyani, Listyaning (Conference on English Language Teaching, 2023)
The pandemic outbreaks enforce students do learning much harder through blended and proper strategy. Cognitive language learning is one of strategy that applied by Indonesian learners in overcoming to cope all English subjects within online blended tool. This study focused on the learners’ preparation and live-process on implementing cognitive strategy on the blended learning classroom. The writers used a qualitative approach empowers by atlas.ti8 with 35 participants of English education study program at Universitas PGRI Semarang, Indonesia and instrumented by observation. Open – ended interview and questionnaire. The result shows the investigation that learners’ preparation are: software of learning, hardware of learning, environment of learning, and time of learning. Otherwise, the learners’ cognitive strategy in blended learning are; listening lecturers’ presentation, watching lecturers’ video presentation. The discussion reveals that Indonesian learners mostly have hardware learning as major need in joining blended classroom, but they don’t have any good preparation on software learning since some of them are not payless. During the pandemic, most of students likely do cognitive strategy through prefer listening to lecturer’s presentation since they might listen while doing anything else (not academic matters). Writers conclude that having English blended classroom learners should consider and provide laptop, smartphone, zoom apps, google meet apps, Wi-Fi, to support their cognitive classroom activities; listening, watching, and presenting materials. We suggest that fulfilling of the well preparation and well joined the English classroom make EFL learners get the knowledge maximally